Impact of renewable energy act reform on wind project finance - Matthew Tisdale; Thilo Grau; Karsten Neuhoff (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
The 2014 reform of the German Renewable Energy Act introduces a mandatory shift from a fixed feed-in tariff to a floating premium system. This is envisaged to create additional incentives for project developers, but also impacts revenues and costs for new investments in wind generation. Thus uncertainties for example about balancing costs and the impact of the location specific generation profile on the average price received by a wind project are allocated to renewable projects. We first estimate the magnitude of the impacts on wind projects based on historic and cross-country comparison. We then apply a cash-flow model for project finance to illustrate to what extent the impact of the uncertainty for project investors reduces the scale of debt that can be accessed by projects and thus increases financing costs.
Keywords: G32; L51; L94; 330; feed in tariff; financing renewables; project finance